2012
DOI: 10.1007/s10802-011-9608-1
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Attachment to Parents and Delinquency

Abstract: To investigate the link between attachment to parents and delinquency, and the potential moderating effects of age and sex, 74 published and unpublished manuscripts (N = 55,537 participants) were subjected to a multilevel meta-analysis. A mean small to moderate effect size was found (r = 0.18). Poor attachment to parents was significantly linked to delinquency in boys and girls. Stronger effect sizes were found for attachment to mothers than attachment to fathers. In addition, stronger effect sizes were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
214
5
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(257 citation statements)
references
References 98 publications
(67 reference statements)
9
214
5
18
Order By: Relevance
“…It was found that male involved more in delinquent behaviors compared to female (Daigle, Cullen & Wright, 2007;Hart & Mueller, 2013;Hoeve et al, 2012). In terms of the severity, female tend to commit less severe behaviors such as lying, stealing, and bullying compared to male who involved in robbery and violent behaviors (Hart & Mueller, 2013;Weerman & Hoeve, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was found that male involved more in delinquent behaviors compared to female (Daigle, Cullen & Wright, 2007;Hart & Mueller, 2013;Hoeve et al, 2012). In terms of the severity, female tend to commit less severe behaviors such as lying, stealing, and bullying compared to male who involved in robbery and violent behaviors (Hart & Mueller, 2013;Weerman & Hoeve, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Children who experience secure attachment with the caregivers and peers result in positive outcomes such as higher self-esteem, better academic achievement, better emotional regulation and higher social competence (Bergin & Bergin, 2009;Hoeve et al, 2012). In contrast, children who experience poor attachment with their caregivers and friends are more likely to result in negative outcome such as behavioral problems and delinquency (Elgar, Knight, Worrall & Sherman, 2003;Hoeve et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da mesma forma, Kazdin (1992) Outros estudos revelaram que reduzida supervisão parental ou supervisão parental inconsistente e a associação com pares desviantes têm emergido como preditores da delinquência entre jovens que vivem em situações de extrema pobreza (Hoeve et al, 2012;Murphy, Brecht, Huang, & Herbeck, 2012;O'Donnell, Richards, Pearce, & Romero, 2012;. Por exemplo, o estudo de Church II, Jaggers e Taylor (2012) indica que a diminuição das taxas de pobreza e o aumento do nível socioeconómico da zona de vizinhança levam a uma diminuição dos comportamentos disruptivos.…”
unclassified
“…De facto, a literatura aponta que uma pobre vinculação aos pais se associa a um maior envolvimento em comportamentos delinquentes (e.g. Hoeve et al, 2012). Quando a qualidade da relação pais-filhos é pobre e quando ocorrem disfunções significativas na família a probabilidade de envolvimento em comportamentos delinquentes é maior, pelo que relações pais-filhos positivas podem funcionar como fatores protetores face à delinquência (Elrod & Ryder, 2014).…”
unclassified